2009
DOI: 10.1111/j.1464-410x.2008.08255.x
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between Gleason scores of needle biopsies and radical prostatectomy specimens: a population‐based study

Abstract: Gleason scores from biopsy and RP specimens. Concordance was evaluated using the κ coefficient, and predictors of concordance were assessed in univariate and multivariate logistic regression analyses. RESULTSThe Gleason scores were identical in biopsy and RP specimens in 591 of the 1116 (53%) patients. The biopsy-based Gleason score more often under-graded (38%) than overgraded (9%) the RP-based Gleason score. Pathology units that examined > 40 RP specimens annually had a higher concordance between the Gleason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 29 publications
(55 reference statements)
8
130
2
6
Order By: Relevance
“…Unfortunately, high-grade PCa may be underestimated on biopsy in up to 38% of cases. [10][11][12][13] Consequently, the reported relationship between DM and tumor grade in the aforementioned studies might not be completely accurate. One recent report examined the relationship between DM and PCa grade in patients who underwent RP.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, high-grade PCa may be underestimated on biopsy in up to 38% of cases. [10][11][12][13] Consequently, the reported relationship between DM and tumor grade in the aforementioned studies might not be completely accurate. One recent report examined the relationship between DM and PCa grade in patients who underwent RP.…”
Section: Discussionmentioning
confidence: 95%
“…Prostate biopsy may misclassify Gleason score in up to 38% of cases. [10][11][12] To the best of our knowledge, this report represents the first European study to examine the relationship between DM and PCa grade in patients undergoing RP. In our study, the rate of DM was lower than that found in the North American reports (7.1 vs 10.2-19.0%).…”
Section: Discussionmentioning
confidence: 95%
“…The comparisons between the results of the histological biopsy compared to the surgical specimen exhibited a correlation equal to ~50% (14)(15)(16)(17). The results of the prostate biopsy and the surgical specimen may differ for several reasons, such as incorrect evaluation by the pathologist, sampling errors and the presence of borderline grading.…”
Section: Discussionmentioning
confidence: 99%
“…Нами использовались сведения о градации по Глисону преимущественно из гистоло-гических заключений, сделанных по биопсийному материалу, так как РПЭ была выполнена только у 19 (17,0 %) из 112 больных. По данным литературы, по-казатель Глисона при биопсии коррелирует с патомор-фологическим заключением после РПЭ только в 30-60 % случаев [18,19]. Возможно, при больших размерах выборки и большей прослеженности боль-ных можно было бы получить достоверные различия в зависимости от градации по Глисону.…”
Section: рис 2 медиана ов больных мкррпж в зависимости от локализацunclassified